2011
DOI: 10.1186/1471-2369-12-49
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to lanthanum carbonate monotherapy effectively controls serum phosphorus with a reduced tablet burden: a multicenter open-label study

Abstract: BackgroundLanthanum carbonate (FOSRENOL®) is an effective, well-tolerated phosphate binder. The ability of lanthanum to reduce serum phosphorus levels to ≤5.5 mg/dL in patients with end-stage renal disease (ESRD) was assessed in a clinical practice setting.MethodsA 16-week, phase IV study enrolled 2763 patients at 223 US sites to evaluate the efficacy of lanthanum carbonate in controlling serum phosphorus in patients with ESRD, and patient and physician satisfaction with, and preference for, lanthanum carbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 14 publications
3
19
2
Order By: Relevance
“…With regard to clinical efficacy, serum phosphate levels after conversion to lanthanum carbonate monotherapy were similar to those achieved with baseline sevelamer hydrochloride monotherapy, in accordance with the results of the primary study of Vemuri et al 25 In a recent analysis of the data from Vemuri et al, we reported that sevelamer hydrochloride and lanthanum carbonate achieved comparable efficacy with an overall dose-relativity ratio of 2.8. 26 The present economic evaluation of dose data from the study by Vemuri In addition to cost saving, conversion to lanthanum carbonate 1000-mg tablets from sevelamer hydrochloride 800-mg tablets would reduce the mean tablet burden by 470%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…With regard to clinical efficacy, serum phosphate levels after conversion to lanthanum carbonate monotherapy were similar to those achieved with baseline sevelamer hydrochloride monotherapy, in accordance with the results of the primary study of Vemuri et al 25 In a recent analysis of the data from Vemuri et al, we reported that sevelamer hydrochloride and lanthanum carbonate achieved comparable efficacy with an overall dose-relativity ratio of 2.8. 26 The present economic evaluation of dose data from the study by Vemuri In addition to cost saving, conversion to lanthanum carbonate 1000-mg tablets from sevelamer hydrochloride 800-mg tablets would reduce the mean tablet burden by 470%.…”
Section: Discussionsupporting
confidence: 88%
“…The study design and patient demographic characteristics were described in detail in the article by Vemuri et al 25 In brief, the primary study was a 16-week, open-label, Phase IV, multicenter study of adult US patients (Z18 years of age) with ESRD who were converted to lanthanum carbonate monotherapy from other phosphate binder regimens. There was an initial screening visit and a 1-week observation period during which patients remained on the previous phosphate binder therapy with no dose modifications permitted.…”
Section: Patients and Methods Primary Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Studies have also reported improved satisfaction among patients with CKD stage 5 when switched from their existing phosphate binder to one with a lower pill burden. 34,35 Tenapanor, administered once or twice daily in milligram quantities, may provide a means to reduce pill burden and mass in patients with hyperphosphatemia, thereby improving adherence to treatment. As is the case with phosphate binders, patients took the study drug (tenapanor or placebo) with meals in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the drug acquisition cost of lanthanum and sevelamer hydrochloride, a post hoc evaluation of cost-effectiveness in non-VA patients was compiled by Keith et al based on a 16-week (phase IV) trial converting sevelamer hydrochloride to lanthanum by Vemuri et al 2,7 The analysis of 691 patients showed an average savings for lanthanum of $11.03 per day based on average wholesale price (AWP) while still maintaining phosphorus control. 2 This cost savings was directly proportional to the dose of sevelamer hydrochloride, with savings beginning with doses greater than or equal to 4,905 mg/day.…”
mentioning
confidence: 99%